New coumestan and coumaronochromone derivatives from Dalbergia boehmii Taub. (Fabaceae). (September 2017) - Abdou, Jean Pierre; Momeni, Jean; Adhikari, Achyut; Tsabang, Nole; Tchinda, Alembert T.; Choudhary, Muhammad I.; Nkengfack, Augustin E.
Graphical abstract: Highlights: Isolation and identification of compounds from Dalbergia bohemii Taub. One new coumestan and one new coumaronochromone derivatives were characterized. Evaluation of the in vitro insulin secretion, in vitro leishmanicidal and anticancer activities of some isolated compounds. Abstract: Chemical investigation of leaves and heartwood of Dalbergia boehmii resulted in the isolation of two new phenolic compounds, designated dalbergestan(1) and dalbergichromone(2), along with eleven known compounds, carpachromene(3), proanthocyanidin A-2(4); piceatannol(5) ; biochanin A(6) ; macckiain(7) ; homopterocarpin(8) ; angolensin(9) ; medicarpin(10) ; 2′, 7-dihydroxy-4′, 5′-dimethoxyisoflavone(11) ; 2′-methoxyformononetin(12) ; and genistein (13 ). The structures of the new compounds were elucidated on the basis of extensive spectroscopic analyses including, IR, UV, 1D and 2D – NMR as well as HRMS data. Some of the isolated compounds were evaluated for their in vitro insulin secretion activity on isolated mice islets, leishmanicidal activity against L. major (DESTO) promastigotes and in vitro cytotoxicity on MCF-7 cell lines. All tested compounds were inactive on glucose-stimulated insulin secretion at stimulatory glucose (20.0 mM) from MIN6 cells. Compounds3 (IC50, 70.0 μg/ml), 6 (IC50, 60.3 μg/ml), 7 (IC50, 86.5 μg/ml) and13 (IC50, 62.6 μg/ml) exhibited low leishmanicidal activity while compound12 (IC50, 56.8 μg/ml) displayed a moderate activity. Compounds3 and5 were found to be active against MCF-7 at 50 μM with IC50 value 33.2 ± 3.79 μg/ml and 42.64 ± 5.05 μg/ml respectively.